Status of the Bean Goose Anser fabalis wintering in central Asia - Heinicke, Thomas (Wildfowl, 2013)
The discovery of Bean Geese Anser fabalis around Lake Issyk-Kul in east Kyrgyzstan in the late 1990s suggested that a little-known Bean Goose population or subspecies wintered in central Asia. A review of published data on Bean Goose numbers and distribution in central Asian countries was undertaken to clarify the historic and current status of Bean Geese wintering in the region. Recent counts suggest that there is a small wintering population of 2,0005,000 birds in central Asia, which is concentrated in a few areas in southeast Kazakhstan, east Kyrgyzstan and northwest China. Assessment of museum specimens of birds collected in central Asia, and also field observations, found that the geese were of the Taiga Bean Goose Anser f. fabalis subspecies. Bean Geese from central Asia have previously been classed as johanseni, but there was no evidence found in the present study for a johanseni subspecies. The lack of regular counts meant that population trends could not be determined with any accuracy, but the small numbers suggest that the population has declined and is now threatened. Formal recognition of the population is important for its management and conservation. Further research into the numbers and distribution of Bean Geese in central Asia is strongly recommended.